”Sensitive” Examination Workshop for Medical Clerkship Students - Glenn Posner (MedEdPORTAL, 2010)
Abstract Introduction When students practice rectal or pelvic examinations on patients, it is difficult for teachers to guide them because the structures being examined cannot be seen. There is also a tendency for students to perform these exams hastily and awkwardly, since they are concerned about causing patient discomfort. At many institutions, part of this training is accomplished using paid gynecologic teaching associates (GTAs), women who allow students to perform pelvic exams on them and teach them how to do so in a respectful manner. A curriculum was designed for a workshop during the preclerkship period to instruct students in the proper technique of physical exam of the breast, female pelvis, male genitalia, and rectum (the “sensitive” exams). Methods The workshop consists of five small-group sessions covering the bimanual pelvic exam, speculum exam and Pap test, breast exam and catheterization, digital rectal exam, and male genitalia exam. The workshop can be administered to approximately 45 students, with each small group containing seven or eight students. The session begins as a large-group session where videos are presented to provide a uniform base of knowledge. The small-group sessions then involve hands-on learning. Results Using a 7-point Likert scale (7 = outstanding), 169 students rated the presenters, the content and the process of the session. Over 70% of students rated each characteristic as a 6 or 7, and over 92% rated each characteristic as a 5 or above. Written comments indicated that the sessions were appreciated and offered constructive feedback to guide future improvements. We then evaluated the effectiveness the female pelvic examination component. 151 students were tested on the bimanual and speculum exams using an objective structured clinical examination. The mean score was 76% with a range of 32%-100%, and only 18 students failed to achieve a score of 60%. Discussion Simulation cannot replace the experience gained from examining a real patient, but given a proper knowledge base, a proper approach to the patient, and extensive practice on models, students will be more comfortable when they do examine real patients. Medical students at our university are now instructed in these sensitive exams using medical simulation models rather than GTAs.